Morquio’s Syndrome: A Case Report of Two Siblings - Sathish Muthukumar Ramalingam; Daya Srinivasan; Sandhya ArunKumar; Joe Louis ChiriyanKandath; Sriram Kaliamoorthy (Case Reports in Dentistry)
Morquio syndrome or MPS IVA is a rare type of lysosomal storage disease associated with highly specific dental abnormalities. We present two siblings with enamel hypoplasia and skeletal abnormalities. A diagnosis of mucopolysaccharidosis type IVA was reached based on the clinical, radiographic, and dental findings of the patients. The dental findings are useful diagnostic aid for the early diagnosis of this debilitating disorder.